MINIMALLY INVASIVE BILIARY DRAINAGE VERSUS PALLIATIVE SURGICAL BILIODIGESTIVE ANASTOMOSES IN MALIGNANT OBSTRUCTIVE JAUNDICE: IMMEDIATE OUTCOMES (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
Malignant obstructive jaundice caused by tumors of the hepatopancreatoduodenal zone is associated with high postoperative morbidity and a mortality of 10–35%. Although endoscopic, percutaneous and combined minimally invasive drainage techniques have largely replaced open palliative surgery, the comparative early safety of these approaches in routine clinical practice — where minimally invasive methods are often applied to the most debilitated patients — requires further evidence.